ANALISIS EFESIENSI PRODUKSI PERTANIAN DENGAN KREDIT USAHA RAKYAT (KUR) BUDIDAYA PERTANIAN TAHUN 2018 (Studi Kasus Pada Kelompok Tani di Kecamatan Pujon dan Ngantang Kabupaten Malang) - SE, Annisa Rosalina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine the efficiency of agricultural production formed by the existence of the people's business credit program (KUR) farms in 2018. This research was conducted with secondary data that was collected by other parties in January 2018-December 2018 which was then analyzed using Data Envelopment Analysis (DEA). The results of this study found that there were some farmers who were said to be efficient in conducting agricultural business after receiving a KUR Tani loan. In addition there are also farmers who are close to efficient, and who are not efficient in carrying out their business. Farmers receiving KUR Tani who are not yet efficient are considered reasonable because they have only become recipients of the KUR Tani program for 1 year so that assistance and training are still needed to be more optimal in carrying out their business. Then the agricultural production has not yet reached a maximum value so that an increase in the capital variable is needed in accordance with the potential improvement value, in line with the additional KUR Tani credit needed. The value of adding KUR Tani credit is intended to increase the shortage of capital from the farmers so that the farmers' agricultural production can increase optimally. In DEA analysis using all data from both input and output shows that the KUR Tani program will lead credit recipients to be more efficient / effective in their farming business. Keywords: Efficiency, Data Envelopment Analysis (DEA), Agriculture, KUR